THE COMPLETE AMINO ACID SEQUENCE OF HUMAN FACTOR V - Jenny, Richard J; Pittman, Debra D; Toole, John J; Kriz, Ronald W; Kaufman, Randal J; Mann, Kenneth G (Thrombosis and Haemostasis, 1987)
cDNA clones encoding human factor V have been isolated and sequenced. The cDNA sequence of factor V obtained from overlapping clones includes a 6672 bp coding region, a 90 bp 5'-untranslated region and a 163 bp 3’-untranslated region including a poly-A tail. The deduced amino acid sequence consists of 2224 amino acids including a 28 amino acid leader peptide. A direct comparison to human factor VIII reveals considerable homology between both proteins with respect to amino acid sequence and domain structure. A triplicated "A" domain and duplicated "C" domain show an approximate 40% identity to the corresponding domains in factor VIII. Factor V and Factor VIII both possess a heavily glycosylated B domain that separates the heavy and light chains of the activated cofactors, although no significant homology is observed in this region. The B domain of factor V contains 35 tandem and approximately 9 additional semi - conserved repeats of nine amino acids of the form (D-L-S-Q-T-T-L-S-P) and 2 additional semi-conserved repeats of 17 amino acids. Factor V contains 37 potential N-linked glycosylation sites, 25 of which are in the B domain, and a total of 19 cysteine residues. By direct comparison to amino acid sequence obtained from both human and bovine factor V, the thrombin (IIa) cleavage sites have been assigned as Arg-709/Ser-710, Arg-1018/Thr-1019, and Are-1545/Ser-1546.(Supported by NIH Grant HL-34575)